2021
DOI: 10.1186/s12877-020-01982-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level, fear of falling and quality of life: a comparison between community-dwelling and assisted-living older adults

Abstract: Background Physical activity (PA), fear of falling (FOF) and quality of life (QOL) are very important constructs in geriatrics. The interplay among these constructs may vary between community-dwelling and assisted-living older adults. However, studies comparing the wellbeing of community-dwelling older adults with those residing in the assisted-living facilities (ALFs) are rather rare especially from developing countries. This study was aimed at comparing PA, FOF and QOL between assisted-living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…High prevalence of fear of falling had been reported in the local environment and world over ( Akosile, Agu et al, 2014 ; Akosile, Anukam et al, 2014 ; Alcolea-Ruiz et al, 2021 ; Tomita et al, 2018 ), and this had been attributed to the negative impact of ageing process on the body systems ( Akosile et al, 2018 ). The mean PA score recorded in this study depicts a low PA level, and falls within the same quartile range previously reported among older adults in different parts of the world ( Akosile et al, 2021 ; Ng et al, 2020 ; Siegmund et al, 2021 ). Physical inactivity had been reported as one of the major public health problems among older adults ( Levinger & Hill, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…High prevalence of fear of falling had been reported in the local environment and world over ( Akosile, Agu et al, 2014 ; Akosile, Anukam et al, 2014 ; Alcolea-Ruiz et al, 2021 ; Tomita et al, 2018 ), and this had been attributed to the negative impact of ageing process on the body systems ( Akosile et al, 2018 ). The mean PA score recorded in this study depicts a low PA level, and falls within the same quartile range previously reported among older adults in different parts of the world ( Akosile et al, 2021 ; Ng et al, 2020 ; Siegmund et al, 2021 ). Physical inactivity had been reported as one of the major public health problems among older adults ( Levinger & Hill, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Participants’ fear of falling had significant negative correlation with each of their general self-efficacy and PA but had positive correlation with their social support. Physical activity had been variously reported to associate negatively with fear of falling ( Akosile, Agu et al, 2014 ; Akosile et al, 2021 ) with both constructs sharing mutual cause-and-effect relationship. However, no previous study is available for referencing on the relationship between fear of falling and general self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Older adults with FOF have reduced activity due to a combination of reduced range of activity, decreased activity frequency, 12 and less frequent outdoor activities, 13 leading to a poor quality of life. 14,15 FOF may be associated with decreased physical and social activity, along with physical conditions such as dizziness, other illnesses, 16 gait function and imbalance, as well as fracture experience, rather than direct fall experience. [17][18][19] The increase in FOF may be due to physical and psychological changes caused by deterioration of physical and social activities during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%